Behavior of Utilization of Posyandu by Mothers Who Have Babies and Toddlers Posyandu Wijaya Kusuma Puskesmas Bahagia: Perilaku Pemanfaatan Posyandu Oleh Ibu Yang Memiliki Bayi Dan Balita Posyandu Wijaya Kusuma Puskesmas Bahagia - Setianingsih, Ajeng; Anggarini, Inggit Meliana; Arifin, Lisa Yulinanda (Universitas Mohammad Husni Thamrin, 2025)
Health services have become one of the uses for society to achieve optimal levels of health individually and in groups. One of these health services is Posyandu. The purpose of this researchKnowing the Relationship between Knowledge, Attitudes and the Role of Cadres on the Behavior of Using Posyandu by Mothers of Babies and Toddlers at Posyandu Wijaya Kusuma Bahagia Health Center, Bekasi Regency in 2023. This research is a quantitative research that uses a cross-sectional research design. The population in this study were all mothers who had babies and toddlers at Posyandu Wijaya Kusuma, totaling 38 people. Sampling was carried out using techniquestotal sampling. The data used in this research is primary data obtained from the results of the questionnaire. The data analysis used is Univariate and Bivariate. The research results showed there was no relationship knowledge (P-Value = 0.452) and the role of cadres (P-Value =0.432) on Posyandu utilization behavior. There is a relationship between attitude (P-Value =0.017) on Posyandu utilization behavior. Advice from researchers is that mothers who have babies and toddlers should take their babies and toddlers to the Posyandu at least once a month when carrying out Posyandu activities. When health education and consultation activities are available, mothers can make good use of these activities